The girl in the park - Fredericks, Mariah (New York : Schwartz & Wade Books, 2012)
When a teenaged girl with a bad reputation is murdered in New York City's Central Park after a party, her childhood friend is determined to solve the mystery of who caused her death.
Kirkus Review
Pub Weekly
Voice of Youth Advocates (V.O.Y.A.)
Kirkus Review, February 2012
Library Media Connection, March 2012
Pub Weekly, February 2012
Keywords: High schools -- Juvenile fiction; Murder -- Juvenile fiction; Schools -- Fiction; High schools -- Fiction; Murder -- Fiction; Mystery and detective stories; Schools -- Fiction; High schools -- Fiction; Homicide -- Fiction; Mystery fiction; School stories; Mystery fiction